2011
DOI: 10.1101/gad.615311
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor receptor 3 directly regulates murine neurogenesis

Abstract: Neural stem cells (NSCs) are slowly dividing astrocytes that are intimately associated with capillary endothelial cells in the subventricular zone (SVZ) of the brain. Functionally, members of the vascular endothelial growth factor (VEGF) family can stimulate neurogenesis as well as angiogenesis, but it has been unclear whether they act directly via VEGF receptors (VEGFRs) expressed by neural cells, or indirectly via the release of growth factors from angiogenic capillaries. Here, we show that VEGFR-3, a recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 48 publications
2
132
1
1
Order By: Relevance
“…2B,C). By contrast, it has been convincingly shown that the closely related factor VEGF-C signals directly to neural stem cells and niche astrocytes through its receptor VEGFR3 (FLT4) independently of its alternative roles in lymphatic or blood vessels (Calvo et al, 2011).…”
Section: Vegf-a and The Angiogenic Niche Of Neurogenesismentioning
confidence: 99%
“…2B,C). By contrast, it has been convincingly shown that the closely related factor VEGF-C signals directly to neural stem cells and niche astrocytes through its receptor VEGFR3 (FLT4) independently of its alternative roles in lymphatic or blood vessels (Calvo et al, 2011).…”
Section: Vegf-a and The Angiogenic Niche Of Neurogenesismentioning
confidence: 99%
“…Vegf-c deletion in the mouse, as well as VEGF-C knockdown in Xenopus tadpoles, inhibited proliferation of neural progenitor cells in the forebrain, without defects of the brain vasculature, indicating that VEGF-C is a trophic factor for subsets of neural progenitor cells in the vertebrate embryonic brain (LeBras et al 2006). The high-affinity VEGF-C receptor VEGFR-3 is also expressed by embryonic and adult neural cells (Choi et al 2010;Calvo et al 2011). Using transgenic VEGFR-3 mice expressing a YFP reporter or conditional deletions of VEGFR-3 in neural cells, we have shown that, in the adult SVZ, VEGF-C/VEGFR-3 signaling acted in niche astrocytes and NSCs to stimulate neurogenesis (Calvo et al 2011).…”
Section: Vegf Signaling In Neuronal Progenitors During Development Anmentioning
confidence: 99%
“…VEGF-B, a VEGFR-2 ligand, has a trophic role in adult neurogenesis, as shown by impaired neurogenesis of Vegf-b-KO mice and the neurogenesis-promoting effect of VEGF-B, which is able to restore neurogenesis in Vegf-b-KO (Sun et al 2006). The lymphangiogenic factor VEGF-C is also expressed in the embryonic (LeBras et al 2006) and adult brain (Shin et al 2008;Calvo et al 2011) in rodents. Vegf-c deletion in the mouse, as well as VEGF-C knockdown in Xenopus tadpoles, inhibited proliferation of neural progenitor cells in the forebrain, without defects of the brain vasculature, indicating that VEGF-C is a trophic factor for subsets of neural progenitor cells in the vertebrate embryonic brain (LeBras et al 2006).…”
Section: Vegf Signaling In Neuronal Progenitors During Development Anmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also believed to act on neural stem/progenitor cells via the VEGF receptor 3 (VEGFR-3) and regulate neurogenesis in developing and adult brains (Calvo et al 2011;Le Bras et al 2006). In addition, VEGF-C/VEGFR-3 is induced in reactive astrocytes, perivascular-infiltrated macrophages, and activated microglia in rats with ischemic stroke and experimental autoimmune encephalomyelitis.…”
Section: Introductionmentioning
confidence: 99%